Development of gnotobiotic system for fish larvae (Barbonymus gonionotus) using iodine, glutaraldehyde, and antibiotic treatments - Haron, Siti Rabi'atul Adawiyyah (2012)
Gnotobiotic system is a system to obtain an organism in axenic condition. In this experiment Javanes barb, Barbonymus gonionotus eggs were used the gnotobiotic model system. Glutaraldehyde, iodine and combination of different antibiotics (rifampicin and gentamicin), were studied to produce gnotobiotic larvae. The effects of the disinfectant on eggs abnormality, hatching rate and bacterial disinfectant were investigated. At high concentration glutaraldehyde >25% and iodine >50 ppm were successful to inhibit the bacterial growth. However, it causes the embryo development to be retarded. At low concentration of glutaraldehyde <25% and iodine <50 ppm, hatching rate was high. However, there were still bacterial growth. In general, the treatment with 25% of glutaraldehyde was the best to obtain gnotobiotic larvae. High survival with no larval deformities were observed using this treatment. It can be concluded that gluteraldehyde at 25% concentration is suitable for future development of Javanese barb gnotobiotic system. The system would allow for better understanding on host-microbial interaction mechanisms.